Next‐generation sequencing study finds an excess of rare, coding single‐nucleotide variants of ADAMTS13 in patients with deep vein thrombosis. Issue 7 (15th July 2013) - Lotta, L. A.; Tuana, G.; Yu, J.; Martinelli, I.; Wang, M.; Yu, F.; Passamonti, S. M.; Pappalardo, E.; Valsecchi, C.; Scherer, S. E.; Hale, W.; Muzny, D. M.; et al.
Summary: Background: The considerable genetic predisposition to deep vein thrombosis (DVT) is only partially accounted for by known genetic risk variants. Rare single‐nucleotide variants (SNVs) of the coding areas of hemostatic genes may explain part of this missing heritability. The ADAMTS 13 and VWF genes encode two interconnected proteins with fundamental hemostatic functions, the disruption of which may result in thrombosis. Objectives: To study the distribution and burden of rare coding SNVs of ADAMTS13 and VWF found by sequencing in cases and controls of DVT. Patients/Methods: The protein‐coding areas of 186 hemostatic/proinflammatory genes were sequenced by next‐generation technology in 94 thrombophilia‐negative patients with DVT and 98 controls. Gene‐specific information on ADAMTS13 and VWF was used to study the association between DVT and rare coding SNVs of the two genes. Results: More than 70 billion base pairs of raw sequence data were produced to sequence the 700‐kb target area with a median redundancy of × 45 in 192 individuals. Most of the 4366 SNVs identified were rare and non‐synonymous, indicating pathogenetic potential. Rare (frequency of < 1%) and low‐frequency (< 5%) coding SNVs of ADAMTS13 were associated with DVT (prevalence 17% vs. 4%; odds ratio [OR] 4.8 and 95% confidence interval [CI] 1.6–15.0 for rare coding; prevalence 36% vs. 23%, OR 1.9 and 95% CI 1.0–3.5 for low‐frequency coding). Patients with rare coding SNVs of ADAMTS13 had lower plasma levels of ADAMTS ‐ 13 activity than patients without them. SNVs of VWF were not associated with DVT. Conclusions: We found an excess of rare coding SNVs of the ADAMTS13 gene in patients with DVT.